2021
DOI: 10.1007/s10902-020-00352-3
|View full text |Cite
|
Sign up to set email alerts
|

Post-Traumatic Growth and Stress-Related Responses During the COVID-19 Pandemic in a National Representative Sample: The Role of Positive Core Beliefs About the World and Others

Abstract: Given the need to understand both the negative and positive psychological consequences of the current global COVID-19 pandemic (Brewin et al.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
150
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 105 publications
12
150
1
5
Order By: Relevance
“…Previous studies have reported positive associations between openness to experience, emotional expression, and posttraumatic growth (e.g., Jaarsma et al, 2006 ). It is possible that e-motions lead to posttraumatic growth by fostering positive core beliefs (e.g., openness to the future and identification with humanity; Vasquez et al, 2021 ; Ellena et al, 2020 ) and emotional strengths (e.g. bravery, humor and social intelligence, Casali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported positive associations between openness to experience, emotional expression, and posttraumatic growth (e.g., Jaarsma et al, 2006 ). It is possible that e-motions lead to posttraumatic growth by fostering positive core beliefs (e.g., openness to the future and identification with humanity; Vasquez et al, 2021 ; Ellena et al, 2020 ) and emotional strengths (e.g. bravery, humor and social intelligence, Casali et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have argued that exposure to the COVID-19 pandemic and its related consequences can also be considered an (individual) traumatic event with almost 20% of adults among the general population suffering posttraumatic stress disorder symptoms during the early stages of the current pandemic (Karatzias et al, 2020 ; Vasquez et al, 2021 ). Vasquez et al ( 2021 ) argued that posttraumatic growth, just after the onset of the pandemic crisis, could be considered an initial coping strategy that allows the development of long-term positive outcomes in personality.…”
Section: Sharing Emotions Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…For example, after the outbreak of COVID-19 epidemic, large-scale social isolation allowed people to have more leisure time, family members could enjoy the warm time of reunion in the family, scientific researchers could have sufficient time to sort out research materials, and professional staff's work and social intercourse also decreased accordingly. A recent study reported that the COVID-19 epidemic could cause people to produce two cognitive model of post-traumatic symptoms (PTS) and post-traumatic growth (PTG) (Vazquez et al, 2021). PTG could enhance people's primal beliefs about the beautiful world, as well as openness to the future and identification with humanity.…”
Section: Conclusion and Prospectmentioning
confidence: 99%
“…Therefore, it seems that positive aspects of functioning and well-being should be seriously considered when analysing the effects of life-threatening events, like a pandemic, if we want to get a more precise picture of the individuals' overall psychological adjustment. There is almost no research on the positive mental health outcomes during a public health crisis or large-scale traumatic events, with the exception of studies on post-traumatic growth (García et al, 2015;Vázquez et al, 2021). Also, the experience of positive emotions during traumatic events may be relevant, as it helps to bounce back (Tugade & Fredrickson, 2004) and to predict positive mental health outcomes (Díaz et al, 2018;Vázquez & Hervás, 2010) .…”
mentioning
confidence: 99%